Revolutionary media in the face of the propagande schème of the French colonialisme in Alegria 1962-1956 - mhamdi, mohamed (Journal of Social Sciences and Humanities, 2021)
This Modest historical study intense, Research shed ding light on one of the important and stratégique fields and Fields dring the Algerian revolutionary période 1954-1962, The issue here is to monitor the Algerian revolutionary efforts in parallèle fields other than the field of armed struggle and the military confrontation with the French soldiers. Where will the study address research in the media and propagande field of this revolution, which is unique from the rest of the prévoies révolutions? The latter, which stood peer to peer for the propaganda arsenal of the French colonial power, Which we find that this decisive media battle between the French and the National Liberation Front, It has taken many different forms and forms, including: petitions, the press, the radio...etc. The latter was able, tanks to a group of loyal fighters to the Algerian cause, Rafting all the fallacieuse of the French colonial propagande against the Algerian revolution, On the other hand, revolutionary radio was able to From introducing the justice and humanity of the Algerian issue to the général libéral and démocrates in various parts of the world.